The Unplaced Fragments of P.Bodmer ii (P66) - Nongbri, Brent (Novum Testamentum, 2018)
Based on autopsy inspection of the fragmentary leaves of P.Bodmer ii (P66), this article assesses previous efforts to properly position the fragments of P.Bodmer ii that were left unplaced in the initial publication of the codex and offers new suggestions for placements.